Enhancing the role of mass media in the translation of evidence from health policy and systems research in Nigeria - Prince Agwu; Chinyere Mbachu; Obinna Onwujekwe (Health Research Policy and Systems)
Abstract Background There are massive gaps in communication between health researchers and policy-makers in Nigeria, which constrains the use of research evidence for policy-making. Mass media can help in bridging the gaps, especially since the media has the reach and a reputation for presenting information in ways that elicit actions from the public and policy-makers. Objective There is a small body of emerging literature from Nigeria and sub-Saharan Africa, evidencing the usefulness of the media to encourage evidence translation in the health sector; and even evidence translation theories are light on dissemination. This paper adds to knowledge on how academia and media can be linked for effective dissemination of evidence for policy impact. Method Data were sourced from group discussions in a communications workshop with 27 participants comprising researchers in health systems and policy and media professionals with several years of experience. Results It was found that health research evidence conducted using quality procedures and published in quality academic journals barely make it to public and policy-making conversations because of the restrictiveness that characterizes academic outputs in traditional academic dissemination outlets. On the basis of the cultivation theory, the media was found instrumental in feedback of research results to communities, securing policy-makers’ reactions and stimulating policy actions. Conclusions In line with message system analysis, researchers must be strategic in the use of mass media, and our results showed how it can be done. In all, media usage for evidence translation has enormous potential to strengthen the health system.